Survival of mammoths (Mammuthus sp.) into the Late Pleistocene in Southwestern British Columbia (Vancouver Island), Canada - Termes, L; Keddie, G; Hebda, R; Trask, P; Arbour, V; Speller, C; Paskulin, L; Ramsey, C; Richards, MR (Canadian Science Publishing, 2024)
As part of a larger project identifying and directly radiocarbon dating Late Pleistocene megafaunal remains in British Columbia (B.C.), Canada we have confirmed the identity of many newly identified mammoth (Mammuthus sp.) specimens (n=32) from Vancouver Island in Southwestern B.C. We undertook radiocarbon dating on all specimens and were able to obtain dates (due to preservation) on 16 of these remains, including re-dating a previously dated mammoth using newer radiocarbon extraction methods. The mammoth dates span a wide range, from >47,500 to 18,000 radiocarbon years BP (uncalibrated). These later new dates support other lines of evidence for portions of Vancouver Island remaining unglaciated towards the end of Late Pleistocene.